Safety Pharmacology of CKD-602, a Novel Anticancer Agent - Kim, Eun Joo; Lee, Rae Kyong; Suh, Jeong Eun; Han, Sang Seop; Kim, Joon Kyum (Arzneimittelforschung, 2003)
CKD-602 ((20S)-7-[2-(N-isopropylamino)-ethyl]-camptothecin · HCl, CAS 213819-48-8) is a new class of anticancer drug that belongs to the topoisomerase inhibitors. Its effect on the central nervous system (CNS), general behavior, cardiovascular-respiratory system and the other organ systems were studied. When intravenously administered, CKD-602 up to doses of 5 mg/kg caused an increase of body temperature, increase of respiration rate, decrease of gastrointestinal transport, showed analgesic action and produced antisecretory action in pylorus ligated rats. However, CKD-602 showed no effects on general behavior, motor coordination, spontaneous locomotor activity, hexobarbital sleeping time, convulsion, cardiovascular, smooth muscle and urinary tract system. These findings demonstrate that CKD-602 in doses up to 5 mg/kg has minor effects on the CNS in animals. However, CKD-602 does not exert any general pharmacological effects at the dose of 1 mg/kg except the effects on gastric secretion.
Keywords: Antitumor agent; Camptothecin derivative; CAS 213819-48-8; CKD-602, cardiovascularrespiratory system, central nervous system, dog, general; pharmacology, guinea pig, mouse, rat; Topoisomerase I inhibitor